KEMAMPUAN ANALISIS PESERTA DIDIK MTs NEGERI 1 MALUKU TENGGARA DALAM MENYELESAIKAN MASALAH MATEMATIKA - Wagola, Nur Hasanah; Mataheru, Wilmintjie (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2023)
Analysis skills is an ability that plays an important role for students in solving a problem. Students must be able to identify an element, apply strategies and conclusions in solving problems, make decisions, arrange problem elements and determine relationships in their settlement. High Order Thinking Skills (HOTS) are thinking skills at a higher level that require students to be able to think critically and creatively by describing parts of the information obtained, finding relationships between parts, constructing and finding solutions to the problems they face. The purpose of this study was to describe students' analytical abilities in solving mathematical problems with the High Order Thinking Skills (HOTS) type in statistics material. This study used a qualitative descriptive research method with the research subjects being class VIII students for the 2021/2022 academic year at MTs Negeri 1 Maluku Tenggara. The instrument in this study was a test item consisting of 2 High Order Thinking Skills (HOTS) questions on statistics. The results of the study showed that students fulfilled the analytical indicator abilities in the differentiating, organizing, and attributing phases